Identifying risk factors for prevalent anal human papillomavirus type 16 infection in women living with HIV. - Elaina Kaufman; Tyler Williamson; Marie-Hélène Mayrand; Ann N Burchell; Marina Klein; Louise Charest; Sophie Rodrigues-Coutlée; François Coutlée; Alexandra de Pokomandy; EVVA study group (PLoS ONE, 2022)
Background Women living with HIV (WLHIV) have a high risk of anal cancer. Identifying risk factors for anal HPV 16 infection, the most significant risk factor for anal cancer, is essential for prevention and screening strategies. Methods In the EVVA Cohort study, 151 WLHIV had cervical and anal HPV testing with genotyping every 6 months for 2 years, while demographic and clinical data were collected via questionnaires and chart reviews. Here, we present results of baseline data analyzed using multivariable logistic regression. Results Among 150 women with adequate HPV test results at baseline, HPV 16 DNA was detected anally in 23 (15.3%; 95%CI:10.4-22.1) and cervically in 5 (3.3%; 95%CI:1.4-7.8). In multivariable analysis, current smoking (OR = 6.0; 95%CI: 1.5-23.9), nadir CD4 count ≤ 200 cells/μL (OR = 8.4; 95%CI: 2.0-34.3), prevalent cervical HPV 16 (OR = 14.7; 95%CI: 1.0-222.5) and anogenital herpes in previous 6 months (OR = 9.8, 95%CI: 1.7-56.8) were associated with prevalent anal HPV 16. Conclusions Knowledge of risk factors can help identify WLHIV at greatest risk of anal HPV 16 infection and, potentially, developing subsequent anal cancer. Identification of the subgroup of these women in whom HPV 16 persists could be an early step in the algorithm of anal cancer screening.